Realizacja reguł gatunku w formie kolekcji w konkretnym przewodniku - Wojtak, Maria (Papers in Linguistics, 2023)
The application of methods of genological analysis in relation to a specific text allows for a formulation of hypotheses about its genre and discursive identity, which broadens the research perspectives of descriptive genology. The analysed text is characterised by an intricate structure, combining a chain and box compositions that may be discovered by referring to the concept of genre in the form of a collection. It includes a profiled description of sanctuaries in a creatively modified convention of Bedeker descriptions and encourages readers to visit specific churches as architectural monuments and places of worship, juxtaposing the perspectives of tourism and pilgrimage. The analysis of a specific text gains a broader cognitive perspective in the article. It allows for reflections, which supplement knowledge about the categories functioning in descriptive genology, such as: genre in the form of a collection, relations between text and genre, as well as between text, genre and discourse, text mosaic and text collage, genre and text hybridizatio and a tourist guidebook as a genre of speech.